2011
DOI: 10.1111/j.1365-2923.2011.04059.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture in medical education: comparing a Thai and a Canadian residency programme

Abstract: This study shows that although the scientific and knowledge base of medical education is universal, its enactment may be influenced by culture and context. Globalisation initiatives in medical education must be tempered by recognition of these considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…While the benefits of introducing such integrated programmes with modern management structures have been well acknowledged [40], the influence of broader social contexts, customs and practices progress of curriculum change is not to be underestimated [41]. A recent study [42] on change from disciplinary to integrated medical curriculum structures in Austria found that while the desire for change, government facilitation and unwavering support from the institution were positive motivators in effecting curriculum change, cultural reluctance towards change, hindrance from authorities and the removal of curriculum reform from institutional priorities resulted in the opposite effect.…”
Section: Discussion: the Warps And Wefts Of An Integrated Matrix-manmentioning
confidence: 98%
“…While the benefits of introducing such integrated programmes with modern management structures have been well acknowledged [40], the influence of broader social contexts, customs and practices progress of curriculum change is not to be underestimated [41]. A recent study [42] on change from disciplinary to integrated medical curriculum structures in Austria found that while the desire for change, government facilitation and unwavering support from the institution were positive motivators in effecting curriculum change, cultural reluctance towards change, hindrance from authorities and the removal of curriculum reform from institutional priorities resulted in the opposite effect.…”
Section: Discussion: the Warps And Wefts Of An Integrated Matrix-manmentioning
confidence: 98%
“…4,5,[51][52][53] However, the impact of organizational culture on change has only been demonstrated in business and health care organizations. [6][7][8][9] To our knowledge, our study is the first to demonstrate this effect in medical schools.…”
Section: Discussionmentioning
confidence: 98%
“…There have been many studies showing the impact of local cultural differences between Western and nonWestern countries on higher education (Watkins & Biggs 2001;Apfelthaler et al 2007;Wong 2011). In response, there has been a growing number of studies regarding cultural differences and context-specific issues, and locally--driven approaches are gaining increased attention in the domain of medical education (Ho et al 2011(Ho et al , 2012Wong 2011;Kikukawa et al 2013;Pan et al 2013;Gosselin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of social sciences, globalization in education has been discussed in terms of two perspectives; global discourses of homogenization and local discourses of culture and context (Wong 2011). According to Holton, homogenization refers to convergence toward a common set of cultural traits and practices (Holton 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation